Kurdistan Regional Goverment : an evaluative study (2003-2011) - Qader, Nazar. H (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
This study examines the internal and external effects of the Kurdistan Regional Government in Northern Iraq. The Kurdish problem in Iraq has been considered the most significant issue in regards to the unity and stability of the country for more than eight decades. However, on the regional level, the establishment of the KRG is considered a threat to the neighbouring states. Based on the concept of autonomy, this study explains the nature of the KRG. This is approached qualitatively by referring to official documents, reports, books, and journals as sources of data. The study found that granting Iraqi Kurds self-governing status by the new Iraqi Constitution in 2005 is considered a key step to resolve the Kurdish problem despite the differences between the Federal Government in Baghdad and the Regional Government in Kurdistan over disputed territories and natural resources that threaten to undermine the political process in the country and destabilize the relationship between the central and regional governments. Additionally, at the regional level, neighbouring states are afraid that the autonomy granted to Iraqi Kurds will motivate other Kurdish populations in those respective countries to make similar demands, which can threaten their territorial integrity and sovereignty. Despite having been awarded autonomy, this study found that an independent Kurdish state in Iraq will not be recognized by regional states, thus, the ambition of the Iraqi Kurds to full independence has yet to be properly realised. In light of this, this study concludes that the Iraqi government should produce a solution that can help resolve the matters disputed between the Federal Government and the Regional Government in Kurdistan in order to achieve the permanent peace.